A Lithium Metal Anode Surviving Battery Cycling Above 200 °C. Issue 29 (28th May 2020) - Fu, Lin; Wan, Mintao; Zhang, Bao; Yuan, Yifei; Jin, Yang; Wang, Wenyu; Wang, Xiancheng; Li, Yuanjian; Wang, Li; Jiang, Jianjun; Lu, Jun; Sun, Yongming
Abstract: Lithium (Li) metal electrode cannot endure elevated temperature (e.g., >200 °C) with the regular battery configuration due to its low melting point (180.5 °C) and high reactivity, which restricts its application in high‐temperature Li metal batteries for energy storage and causes safety concerns for regular ambient‐temperature Li metal batteries. Herein, this work reports a Li5 B4 /Li composite featuring a 3D Li5 B4 fibrillar framework filled with metallic Li, which maintains its initial structure at 325 °C in Ar atmosphere without leakage of the liquid Li. The capillary force caused by the porous structure of the Li4 B5 fibrillar framework, together with its lithiophilic surface, restricts the leakage of liquid metallic Li and enables good thermal tolerance of the Li5 B4 /Li composite. Thus, it can be facilely operated for rechargeable high‐temperature Li metal batteries. Li5 B4 /Li electrodes are coupled with a garnet‐type ceramic electrolyte (Li6.5 La3 Zr0.5 Ta1.5 O12 ) to fabricate symmetric cells, which exhibit stable Li stripping/plating behaviors with low overpotential of ≈6 mV at 200 °C using a regular sandwich‐type cell configuration. This work affords new insights into realizing a stable Li metal anode for high‐temperature Li metal batteries with a simple battery configuration and high safety, which is different from traditional molten‐salt Li metal batteries using a pristine metallic Li anode. Abstract : A Li5 B4 /Li composite is explored as a stable anode for rechargeable high‐temperature Li metal batteries. Benefiting from the effect of capillary and physical confinement of the porous lithiophilic Li5 B4 framework for liquid metallic Li, the Li5 B4 /Li composite maintains its initial structure and shows stable electrochemical cycling at 200 °C with a regular cell configuration.